Comparison of muscle synergies in walking and pedaling: the influence of rotation direction and speed - Tsuchiya, Junko; Momose, Kimito; Saito, Hiroki; Watanabe, Koji; Yamaguchi, Tomofumi (Frontiers in Neuroscience, 2024)
BackgroundUnderstanding the muscle synergies shared between pedaling and walking is crucial for elucidating the mechanisms of human motor control and establishing highly individualized rehabilitation strategies. This study investigated how pedaling direction and speed influence the recruitment of walking-like muscle synergies.MethodsTwelve healthy male participants pedaled at three speeds (60 RPM, 30 RPM, and 80 RPM) in two rotational directions (forward and backward). Additionally, they completed walking tasks at three different speeds (slow, comfortable, and fast). Surface electromyography (EMG) was recorded on 10 lower limb muscles during movement, and muscle synergies were extracted from each condition using non-negative matrix factorization. The similarities between the muscle synergies during walking and each pedaling condition were examined using cosine similarity.ResultsThe results confirmed that the composition of muscle synergies during pedaling varied depending on the rotational direction and speed. Furthermore, one to three muscle synergies, similar to those observed during walking, were recruited in each pedaling condition, with specific synergies dependent on direction and speed. For instance, synergy involving the quadriceps and hip extensors was predominantly observed during pedaling at 30 RPM, regardless of the direction of rotation. Meanwhile, synergy involving the hamstrings was more pronounced during forward pedaling at 60 RPM and backward pedaling at 80 RPM.ConclusionThese findings suggest that walking-like muscle synergies can be selectively recruited during pedaling, depending on the rotational direction and speed.